Lactiplantibacillus pentosus P2020 protects the hyperuricemia and renal inflammation in mice - Wang, Zhihuan; Song, Liqiong; Li, Xianping; Xiao, Yuchun; Huang, Yuanming; Zhang, Yue; Li, Jintong; Li, Mingding; Ren, Zhihong (Frontiers in Nutrition, 2023)
Introduction Hyperuricemia (HUA) is a common metabolic disease, and its prevalence has been increasing worldwide. Pharmaceutical drugs have been used for controlling HUA but they all have certain side effects, which thus calls for discovering alternative options including using treatment of probiotics to prevent the development of HUA. Methods We established HUA mice model induced by potassium oxonate and adenine and performed in vivo experiments to verify the ability to lower serum uric acid of Lactiplantibacillus pentosus P2020 (LPP), a probiotics stain extracted from Chinese pickle. We also tried to discussed the underlying mechanisms. Results Oral administration with LPP significantly decreased serum uric acid and reduced renal inflammatory response by downregulating multiple inflammation pathways including NK-kB, MAPK, and TNFα. We also found that LPP administration significantly promoted uric acid excretion by regulating expression of transporters in the kidney and ileum. In addition, LPP intake improved intestinal barrier function and modulated the composition of gut microbiota. Discussion These results suggest that probiotics LPP may have a promising potential to protect against development of HUA and HUA-related renal damage, and its working mechanisms involve regulation of inflammation pathways and expression of transporters in the kidney and ileum.